Impact of United States Political Uncertainty on Rupiah Fluctuations and Indonesia’s Monetary Indicators - Pratama, Zanuar Zaki; Fafurida, Fafurida (Jayapangus Press, 2025)
This study analyzes the macroeconomic factors influencing the Rupiah exchange rate against the US Dollar (USD/IDR) in Indonesia, considering that exchange rate volatility can affect economic stability. The dynamics of imports, exports, money supply (M2), inflation, and Bank Indonesia's (BI) benchmark interest rate are believed to play a crucial role in currency movements. The primary objective of this research is to analyze the long-term and short-term effects of these variables on the USD/IDR exchange rate in Indonesia. This study is quantitative in nature, using time series data and applying the Error Correction Model (ECM) to identify long-term relationships among variables as well as short-term adjustment mechanisms. The analysis results indicate that in the long run, Money Supply (M2), inflation, and BI interest rates have a significant positive relationship with the exchange rate (Rupiah depreciation), while imports and exports show a significant negative relationship (Rupiah appreciation). In the short term, changes in all independent variables also significantly affect exchange rate movements, with M2, inflation, and BI interest rates causing depreciation, while imports and exports cause appreciation. A significant error correction value indicates the presence of an adjustment process to return to long-term equilibrium. The implications of this study highlight the importance of managing the money supply, controlling inflation, and implementing balanced trade policies in maintaining Rupiah exchange rate stability, as well as the understanding that BI interest rate hikes are often a response to existing depreciation pressures.